Personal Characteristics and Personality-Temperament Traits and Its Implications to Effective Leadership in Organizations - Olila, Rowel (JPAIR Multidisciplinary Research, 2020)
Trait leadership theory is an integrated pattern of personal characteristics that reflects a range of individual differences and fosters consistent leader effectiveness across various groups and organizational situations. A leader would lead people following his personality characteristics and traits. This quantitative-correlational research investigated the significant difference in the personal characteristics and personality-temperament traits of the 141 Educators from the public and private schools in Aurora, Philippines. A questionnaire was used to describe the personal characteristics of the respondents. The prevailing traits among the respondents were assessed using a checklist. The research utilized statistical techniques such as frequency count, percentages, and chi-square test. Analyzed data revealed that a majority of the educators had a choleric temperament. Furthermore, personality-temperament traits of the educator varied significantly when they were grouped by gender (c2 = 48.674), age (c2 = 45.240), civil status (c2 = 15.047), educational attainment (c2 = 50.752), and length of service (c2 = 15.960). Thus, the Educators are ambitious and leader-like, and that personal characteristics were significant factors in differentiating the respondents’ personality-temperament traits.